1994
DOI: 10.1002/macp.1994.021950601
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric liquid‐crystalline elastomers

Abstract: Oriented liquid-crystalline (LC) elastomers (polar monodomains, concerning the direction of polarisation) have been prepared from polar monodomains of ferroelectric LC-polysiloxanes by a radical photocrosslinking process. Attempts to perform ferroelectric switching lead in these soft elastomers to an elastic stress which prohibitsfor low voltagesa complete reorientation of the polar axis (ferroelectric switching). A ferroelectric switching can, however, be observed for high voltages. The loop of hysteresis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(108 citation statements)
references
References 10 publications
2
101
0
2
Order By: Relevance
“…Previous studies on the elastomers of terpolymer P2 show a successful stabilization of one ferroelectric switching state, when the crosslinking reaction takes place in the smectic-C* phase with applied d.c.-field 11,12) . Afterwards a switching of the mesogens in the second, unfavored switching-state is still possible.…”
Section: Stepwise Crosslinking Of Terpolysiloxane P2 In the Smectic Cmentioning
confidence: 98%
“…Previous studies on the elastomers of terpolymer P2 show a successful stabilization of one ferroelectric switching state, when the crosslinking reaction takes place in the smectic-C* phase with applied d.c.-field 11,12) . Afterwards a switching of the mesogens in the second, unfavored switching-state is still possible.…”
Section: Stepwise Crosslinking Of Terpolysiloxane P2 In the Smectic Cmentioning
confidence: 98%
“…Various methods of alignment are used to obtain single-crystal monodomains, which ensure these elements act together. Shearing surface force [44], electrical [180] and magnetic fields [61] are all well-known methods for aligning mesogens before initiating polymerisation to preserve this orientation. Photoalignment can create spatially varying responses in two dimensions, demonstrated both continuously [181,182] and using a discrete voxel approach [60].…”
Section: Reproducing Positioning and Orientationmentioning
confidence: 99%
“…The formation of an elastic network leaves the phase sequences and many anisotropic properties nearly unaffected, but it introduces a coupling between the orientation of the mesogens and macroscopic elastic deformations of the network. Ferroelectric smectic phases, due to their strong interactions with electric fields, open the possibility to switch the mesogenic orientation even in presence of the network [2]. A typical ferroelectric hysteresis can be measured.…”
Section: Introductionmentioning
confidence: 97%
“…A typical ferroelectric hysteresis can be measured. It has been shown that the switching properties of ferroelectric LCE depend strongly on the network topology [2,3]. The dynamics and mechanical properties of ferroelectric LCE have been investigated with various experimental methods, for example with dielectric spectroscopy [6] Michelson-interferometry [4], Fourier transform IR [5] and AFM [7].…”
Section: Introductionmentioning
confidence: 99%